A forecast evaluation of the Riksbank's policy‐rate projections. (17th May 2020) - Nordström, Martin
Abstract: This paper evaluates the forecasting performance of the policy‐rate path published by the Swedish central bank, the Riksbank. Using data from 2007 to 2019, I find that the Riksbank's forecast has been relatively inaccurate compared to a forecast inferred from market pricing. My analysis indicates that this result is primarily driven by events during the period 2010–2014. This coincides with a period during which the Riksbank arguably "leaned against the wind" and a potential link is discussed in the paper.